A Mini-Review on Lichen-Based Nanoparticles and Their Applications as Antimicrobial Agents - Rattan, Rohit; Shukla, Sudeep; Sharma, Bharti; Bhat, Mamta (Frontiers in Microbiology, 2021)
Nanotechnology is proving to be a revolutionary tool for the development of antimicrobial materials required in the healthcare sector. While green chemistry based techniques are hailed for their eco-friendliness and cost-effectiveness, the lichen based nanoparticles, particularly, are becoming increasingly popular. Nanoparticles derived from different lichens have been found to exhibit significant antimicrobial properties. These lichen based metal nanomaterials have emerged as promising alternatives to traditional antimicrobial therapies. The present mini review summarizes an overview of lichen-based nanomaterials, their synthesis, applications and molecular mechanism of their potential as broad spectrum antimicrobial agents.